Influence of dextrins on the production of spiramycin and impurity components by Streptomyces ambofaciens - Yao, Kaiya; Gao, Shuhong; Wu, Yanjie; Zhao, Zhen; Wang, Wen; Mao, Quangui (Folia microbiologica, 2018)
Spiramycin is a 16-membered macrolide antibiotic produced by Streptomyces ambofaciens and used in human medicine for the treatment of various respiratory tract and genital infections. Several impurities were detected in spiramycin-fermentation broth, especially impurities D and F, which decreased the separation-extraction yield and increased production cost. Dextrins, as the main carbon source, influence the accumulation of spiramycin and impurities. In this work, two types of dextrin from vendor Y and Z were compared to study their influences on spiramycin production. Our results showed that final spiramycin production with dextrin Z was enhanced twofold as compared with dextrin Y; however, the content of impurities F and D were higher with dextrin Z relative to dextrin Y. Several parameters (adenosine triphosphate, total sugar, reducing sugar, and reducing sugar to total sugar) were analyzed to reveal differences in the fermentation process. In vitro dextrin hydrolysis by amylase revealed structural differences in the two types of dextrin, and real-time quantitative polymerase chain reaction analyses showed that the transcription of srm7 and srm21 (involved in forosaminyl methylation) was enhanced and potentially related to the reduced formation of impurity F with dextrin Y. Furthermore, the srm20/srm33 ratio, representing flux balance of forosaminyl and mycarosyl, was ~ 1, implying that forosaminyl and mycarosyl biosynthesis were well balanced, resulting in reduced production of impurity D with dextrin Y.
Keywords: Dextrins; Anti-Bacterial Agents; Streptomyces; antibakteriální látky; spiramycin; dextriny; Drug Contamination; kontaminace léku; Spiramycin